419OOlanzapine combined with 5-HT3 RA plus dexamethasone for prevention and treatment of chemotherapy-induced nausea and vomiting in cancer patients: A systematic review and meta-analysis of randomized controlled trials. (24th November 2019) - Zhou, J-G; Jin, S-H; Ma, H
Abstract: Background: We conducted a review to evaluate the efficacy and adverse events (AEs) of olanzapine combined with 5-hydroxytryptamine type 3 (5-HT3) receptor antagonist (RA) plus dexamethasone compared with 5-HT3 RA plus dexamethasone for the prevention and treatment of chemotherapyinduced nausea and vomiting (CINV) in high and moderate emetogenic chemotherapy based on randomized controlled trials (RCTs). Methods: PubMed, Web of Science, EMBASE, and The Cochrane Library, WanFang Database, China Biomedical Literature database (CBM), China National Knowledge Infrastructure (CNKI), and Chinese Science and Technology Periodical Database (VIP) (inception to April 2019) were searched to recognize relevant articles. Relative risk (RR) with 95% confidence intervals (CIs) for CINV and AEs were all extracted. Results: 11 studies with 1107 cancer patients were involved in this review. The pooled RR of any level acute CINV (RR = 0.60, 95%CI: 0.48–0.75, Z=-4.57, P < 0.01) and any level delayed CINV (RR = 0.50, 95%CI: 0.38-0.66, Z=-4.87, P < 0.01) were significantly decreased in olanzapine group. While only CINV III and CINV IV were significantly decreased in olanzapine groups. Subgroup analysis indicated that there was no significant difference between 5mg and 10mg for olanzapine. Moreover, the occurrence of insomnia (RR = 0.12, 95%CI: 0.06-0.26, Z=-5.44, P < 0.01) was statistically decreased in the olanzapine group. Conclusions: Olanzapine significantly decreased the occurrence of moderate-severe CINV (CINV III and IV) and insomnia for the prevention and treatment of CINV in high and moderately emetogenic chemotherapy. Compared with 10mg per day, 5mg oral may be more appropriate for cancer patients. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.